ANALISIS TERHADAP PENYALAHGUNAAN ALOKASI DANA DESA DIKAITKAN DENGAN TINDAK PIDANA KORUPSI - Efensius Bali; Syawal Amry Siregar; Maurice Rogers (JURNAL RETENTUM, 2020)
This research aims finding criminal action of corruption and punishment for the defendant at Dusun I Desa Percut Kecamatan Percut Sei Tuan Kabupaten Deli Serdang based on the verdict No. 125/Pid.Sus.TPK/2017PN.Mdn. The key instrument in this study is the researcher himself and this study uses data analysis techniques that are qualitative descriptive. The main instrument in this research is the research doer where the analysis technique of this research is qualitative descriptive. The result of this research showed that the allocating of the village fund (Dana Desa) had been miss-used and the defendant’s accusation was five years, arrested in prison, and paid the lawsuit five thousand Rupiah.